Analisis Gaya Kepemimpinan Demokratis di UMKM Belia House Kab. Langkat - Nanda Ayu Setiawati, Fadhilah Syam Nst, Elvi Mailani, Dian Armanto (LPPPI Publishing, 2022)
Leadership style talks about how a leader applies his leadership. While the value of leadership is a principle held by leaders in the application of leadership. The democratic leadership style makes human resources a core and main component in the organization. All human resources in the organization will have value and are valuable if they have the competence, willingness, mind, and interest and have attention and have different views with other people in the organization. In this study, it aims to see an interesting phenomenon to study that the democratic leadership style is able to develop and advance the development of Belia House. This study will use a descriptive qualitative approach. The author does this because there are several things that require direct investigation of the informant. According to Jane Richie, qualitative research is an attempt to present the social world and its perspective in the world, in terms of concepts, behaviors, and issues, about the human being studied. The democratic leadership style places more emphasis on high support in decision-making and policy with little direction. A good leadership factor will be the control of problem solving in an organization. Democratic leadership in MSME Belia House can encourage employee performance and motivate them to excel by listening to input from all parties, both leaders and subordinates.